'A Portrait of Lower Silesia': Researching identity through collodion photography and memory narratives. Issue 3 (November 2019) - Sidorenko, Ewa
In this article, I discuss a performance arts–based visual methodology based on the use of the archaic wet collodion photography. The collaboration between Street Collodion Art photography collective and myself, as a researcher, had two aims: to generate a large scale photographic and narrative portrait of Lower Silesia in Poland, and to explore identities in the region where nearly all of its inhabitants represent recent migrant populations. Data generated through this project include collodion portraits, their interpretations and narratives collected through unstructured interviews. Initial data analysis has generated identity narratives linked to work, place and belonging and ethnicity/nationality. In addition, in 2016 and 2017, three exhibitions of the portraits and a selection of edited stories took place in Lubin, Legnica and Wrocław attended by local inhabitants, including project participants. The examination of the arts-based methodology finds that the ritual character of the wet collodion photographic encounter has acted as a form of artistic intervention which, in generating memory narratives, enabled an articulation of social identities in the climate dominated by nationalist discourses. Such symbolic work emerging out of the project reveals a critical potential in the collaboration between the arts and social research. Furthermore, the project has shown that despite different traditions of practice, a collaboration between the artists and social researchers can yield rich data and access participants in ways that conventional methodologies cannot.